Femvertising Discourse in The Body Shop Indonesia Campaign . Discourse Analysis Study of The Body Shop Indonesia Campaign Stop Sexual Violence #TBSFightForSisterhood : Diskursus Femvertising Dalam Kampanye The Body Shop Indonesia. Studi Analisis Wacana Kampanye The Body Shop Indonesia Stop Sexual Violence #TBSFightForSisterhood - Agnes Devita Yuli; Poppy Febriana (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to describe femvertising in The Body Shop Indonesia Stop Sexual Violence #TBSFightForSisterhood Campaign. This research method uses qualitative, data collection is carried out by observation, namely observing uploads on Instagram @thebodyshopindo.impact. The data analysis technique uses a critical discourse analysis model of Norman Fairclough. The results of this study indicate that, most of the uploads in femvertising in The Body Shop Indonesia Campaign entitled Stop Sexual Violence use words that form public awareness of the urgency of sexual violence cases, describe women's dominance as objects of sexual violence, campaigns that are wrapped with sexual violence education so that they reap the benefits of sexual violence. public response, and gain public attention for the achievement of the campaign's objectives.